Clinical characteristics of fetal and neonatal outcomes in twin pregnancy with preeclampsia in a retrospective case–control study: A STROBE-compliant article. Issue 43 (October 2016) - Yuan, Ting; Wang, Wei; Li, Xue-Lan; Li, Chun-Fang; Li, Chao; Gou, Wen-Li; Han, Zhen
Abstract : Abstract: The aim of our study was to compare the clinical characteristics of fetal and neonatal outcomes in twin pregnancies between women with preeclampsia (PE) and those with normotension in a Chinese population. There were 143 preeclamptic women and 367 normotensive women with twin pregnancies included in this retrospective case–control study. The baseline characteristics and perinatal outcomes were collected and compared between the groups. Multiple logistic regression and linear regression were used to assess the correlations between PE and the outcomes. Significant increases were observed in the frequencies of preterm delivery (OR = 2.75, P < 0.001), iatrogenic preterm birth (OR = 3.52, P < 0.001), and IUGR (OR = 2.94, P = 0.001) in the PE group, and the PE group had more than a 2-fold risk of adverse neonatal outcomes. Preeclamptic twin neonates had lower birth weights (β = −147.34, P = 0.005; β = −169.47, P = 0.001). The comparison on the discordance of intertwin weight was not significantly different. Twin pregnancies with PE are associated with worse perinatal outcomes. The adverse outcomes of preeclamptic twin pregnancies may be associated with lower birth weights rather than the discordance of the intertwin weight, which requires further confirmation. The results may provide helpful references for better clinical assessments, evaluations of prognosis, and a deeper understanding of preeclamptic twin pregnancies.